Structural reliability analysis of in-service API X65 natural gas pipeline using statistical data - Baek, Jong-hyun; Jang, Yun-chan; Kim, Ik-joong; Yoo, Jung-soo; Kim, Cheol-man; Kim, Young-pyo (The International journal of pressure vessels and piping, 2022)
The failure probability of the pipeline in the structural reliability assessment was evaluated by the relationship between the resistance of the pipe material to an external load or stress. The stress acting on the natural gas pipeline is affected by the circumferential stress and the longitudinal stress generated by the internal pressure, the thermal stress caused by the temperature difference during installation and operation, the bending stress caused by the buried depth, the embankment height, and vehicle load. The failure probabilities of the API X65 pipes were evaluated by the Von-Mises stress criterion as the maximum allowable stress criterion under the combined stresses. First-order reliability method as approximate analytical methods was used to perform the failure probability analysis on the natural gas pipelines. The failure probabilities of the pipelines were evaluated with buried depth in a range of 1.5–30 m and wheel load in the range of 2.5–20 ton. The failure probabilities were evaluated under the conditions that internal pressure of 7 MPa, temperature difference of −45 °C, soil density of 18.9 kN/m3. •Random variables such as average, standard deviation and coefficient of variation were employed from the mill sheets and operation conditions actually used in the natural gas utilities.•Probability of failure due to the yielding of the API X65 natural gas pipe with the average tensile strength of 515 MPa is 2.44E-21.•Probability of failure due to the bursting of the API X65 natural gas pipe with the average tensile strength of 594 MPa is 3.28E-32.•Probability of failure to the API X65 natural gas pipe due to external loads such as soil load and vehicle load change was evaluated.